Cooperative, Collaborative, and Related Strategies’ Effect on Learning in Children with Autism (Global Journal of Medical Research, 2023)
When the right circumstances are met children with autism can engage in settings for general education and have a successful educational career A truly inclusive learning environment and research-based inclusion techniques must be in place for children with autism to be successfully included The research studies that concentrate on cooperative and collaborative learning methodologies are reviewed in this article The article concludes by outlining the need for additional study This study examined 29 research studies using cooperative collaborative and related techniques with children with autism Each article had to meet these requirements to be included 1 describe the use of an evidence-based intervention for at least one participant with ASD 2 Consist of at least one collaborative cooperative or related method 3 Research needed to be conducted in an inclusive setting and finally 4 The reviewed articles had to have been released in 2010 or later
Keywords: inclusion; cooperative learning; collaborative learning; children with autism